Designing appropriate complementary feeding recommendations: tools for programmatic action. Issue 3 (18th September 2013) - Daelmans, Bernadette; Ferguson, Elaine; Lutter, Chessa K.; Singh, Neha; Pachón, Helena; Creed‐Kanashiro, Hilary; Woldt, Monica; Mangasaryan, Nuné; Cheung, Edith; Mir, Roger; Pareja, Rossina; Briend, André
Abstract: Suboptimal complementary feeding practices contribute to a rapid increase in the prevalence of stunting in young children from age 6 months. The design of effective programmes to improve infant and young child feeding requires a sound understanding of the local situation and a systematic process for prioritizing interventions, integrating them into existing delivery platforms and monitoring their implementation and impact. The identification of adequate food‐based feeding recommendations that respect locally available foods and address gaps in nutrient availability is particularly challenging. We describe two tools that are now available to strengthen infant and young child‐feeding programming at national and subnational levels. Pro PAN is a set of research tools that guide users through a step‐by‐step process for identifying problems related to young child nutrition; defining the context in which these problems occur; formulating, testing, and selecting behaviour‐change recommendations and nutritional recipes; developing the interventions to promote them; and designing a monitoring and evaluation system to measure progress towards intervention goals. Optifood is a computer‐based platform based on linear programming analysis to develop nutrient‐adequate feeding recommendations at lowest cost, based on locally available foods with the addition of fortified products or supplements when needed, or best recommendations when the latter are not available. The tools complement each other and a case study from Peru illustrates how they have been used. The readiness of both instruments will enable partners to invest in capacity development for their use in countries and strengthen programmes to address infant and young child feeding and prevent malnutrition.